Measuring Mental Wellness of Adolescents: A Systematic Review of Instruments - Orth, Zaida; Moosajee, Faranha; Van Wyk, Brian (Frontiers in Psychology, 2022)
Objective Mental health is critical to the healthy development of adolescents. However, mental health encompasses more than the absence of mental illness; and should include indicators of mental wellness. A critical review of available mental wellness instruments for adolescents were conducted to identify operational definitions of mental wellness concepts for this population group. Method A systematic review of literature published between 2000 and 2020 was done to identify mental wellness instruments for adolescent populations. The review followed the PRISMA operational steps. Results We identified 2,543 articles from the search strategy and screened titles and abstracts for eligibility. After appraisal, 97 studies were included in the qualitative synthesis; of which, 79 mental wellness instruments were identified. Most studies did not provide a definition for mental wellness. We identified thirteen mental wellness concepts from 97 studies, namely: life satisfaction, mental wellbeing [general], resilience, self-efficacy, self- esteem, connectedness, coping, self-control, mindfulness/spiritual, hope, sense of coherence, happiness, and life purpose. Conclusion The review reflected previous research identifying a lack of consensus around the definitions of mental health, mental wellness, and mental wellbeing. This has implications for developing instruments for adolescents that adequately measure these constructs. Most of the instruments identified in the review were predominantly English and from developed countries. This indicates a need for instrument that are explicitly conceptualised and operationalised for adolescents in all their varied contexts.